Gracejando das filhas de Eva : a mulher burguesa em anedotas oitocentistas - Rabelo, Aline Augusta Rocha (2015)
This thesis has as object the image of the nineteenth-century bourgeois woman. The research used as a primary source a set of 46 anecdotes published in Aracaju newspapers between 1889 1897. The goal is to sort, examine and interpret those images with regard to the concepts of Stereotype (Marie Jahoda), Representation (Roger Chartier), Male Domination, Symbolic Violence (both by Pierre Bourdieu) and Patriarchalism (Jean-François Dortier and Gilberto Freyre). This paper adopts the methodology of Cultural History proposed by Robert Darnton (1984). The results of the research are: the jokes about women should be understood in the context of contention between the genders; the authors of the jokes fought the public behaviors of women through the ridicule; anecdotes update old stereotypes about women, and should be understood in a context where the bourgeois woman leaves home and the risk of deviations are larger. The laughter against women, expressed in jokes, is a manifestation from the so-called "male domination" and can be regarded as a representation, for it has a group origin, and it´s a weapon of political struggle between genders. Finally, the nineteenth-century anecdotes about women express an old function of the humor: punish the customs.